2018
DOI: 10.1111/jan.13897
|View full text |Cite
|
Sign up to set email alerts
|

Intentional rounding – An integrative literature review

Abstract: Aims To establish current knowledge about the efficacy and acceptance of intentional rounding in current practice, from the perspective of nurses, patients, patient satisfaction and safety indicators. Background Intentional rounding is a formal means of nursing staff checking care needs of patients in hospital settings on a regular basis. Design An integrative literature review conducted following the Joanna Briggs Institute manual. Data sources A literature search from 2000 – 2017 was conducted using the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…In this review, interventions that promoted routine communication activities, like bedside handover appeared to provide intentional and set opportunities for patient engagement in assessment, choice/decision‐making, information‐sharing and goal‐setting dialogue. Bedside handover, intentional rounding and ward rounds are all routine communication activities that provide opportunities for shared dialogue with patients; however, researchers have shown that implementing these activities does not necessarily equate to patient engagement (82–84). Instead, nurses can become task‐orientated during these activities, gaining the information they require from patients without sufficient patient engagement (82–84).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, interventions that promoted routine communication activities, like bedside handover appeared to provide intentional and set opportunities for patient engagement in assessment, choice/decision‐making, information‐sharing and goal‐setting dialogue. Bedside handover, intentional rounding and ward rounds are all routine communication activities that provide opportunities for shared dialogue with patients; however, researchers have shown that implementing these activities does not necessarily equate to patient engagement (82–84). Instead, nurses can become task‐orientated during these activities, gaining the information they require from patients without sufficient patient engagement (82–84).…”
Section: Discussionmentioning
confidence: 99%
“…Bedside handover, intentional rounding and ward rounds are all routine communication activities that provide opportunities for shared dialogue with patients; however, researchers have shown that implementing these activities does not necessarily equate to patient engagement (82–84). Instead, nurses can become task‐orientated during these activities, gaining the information they require from patients without sufficient patient engagement (82–84). For routine communication activities to be truly patient‐centred, nurses must incorporate information shared by the patient into the care plan (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hourly rounding allows nurses to move from a reactionary to an anticipatory approach to meeting patient needs in a timely fashion (Tea et al, 2008). Previous studies have found that intentional rounding significantly reduces call bell use which gives nursing staff more time to care for their patients and be more responsive when a call bell rings (Meade, Bursell, & Ketelsen, 2006;Mitchell et al, 2014;Ryan et al, 2019).…”
Section: Re Sultsmentioning
confidence: 99%
“…One intervention that could be used for both prevention and identification of RTAC in a care bundle is intentional rounding. Intentional rounding is a formal, systematic approach that involves regular checking of individual patients by nursing staff (Ryan, Jackson, Woods, & Usher, 2019). The goals of intentional rounding include anticipating patient needs (e.g., toileting, pain, and comfort), reducing adverse advents (e.g., falls and pressure injury), reducing patient anxieties (Ryan et al, 2019), and strengthening the therapeutic relationships between nursing staff and their patients (Maddigan, Butler, & Davidson, 2019).…”
Section: Preventing Avoidable Rtacmentioning
confidence: 99%